An acrylate-modified polyester resin, its preparation method and use
Patent Information
- Application Number
- CN202510859071.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-25
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2045-06-25
AI Technical Summary
然而,其非极性分子结构导致粘接性能极差,成为工业应用中长期存在的技术瓶颈
[0033]本发明通过以具有多官能团的酸酐和长碳链不饱和单官醇为原料,合成不饱和中间单体,再将该中间单体与常规二元酸、二元醇继续酯化、缩聚得到含有不饱双键的聚酯树脂中间体,随后将丙烯酸酯单体接枝引入树脂中间体体系中,进而得到一种对非极性基材(如PP或PE材料)具有很强粘接性能的改性树脂。
Smart Images

Figure QLYQS_1 
Figure QLYQS_2 
Figure BDA0005466899260000021
Abstract
Description
Technical Field
[0001] This invention relates to the field of polymer materials, specifically to an acrylate-modified polyester resin, its preparation method, and its applications. Background Technology
[0002] PP (polypropylene) and PE (polyethylene), as non-polar polymer materials, are widely used in construction, automotive, electronics, packaging, and medical fields due to their excellent chemical stability, corrosion resistance, lightweight, and low cost. However, their non-polar molecular structure results in extremely poor adhesive properties, which has long been a technical bottleneck in industrial applications. PP / PE is composed only of carbon and hydrogen atoms and lacks polar groups (such as hydroxyl and carboxyl groups), making it unable to form chemical bonds or hydrogen bonds with conventional adhesives. This leads to insufficient interfacial bonding, and its surface energy is only 30-34 mN / m, making it difficult for adhesives to wet and spread. Contact angle tests show that the liquid easily shrinks into a spherical shape.
[0003] CN104893648B discloses a polyamide hot melt adhesive with strong adhesion to non-polar materials, which is prepared using aliphatic diamines, alicyclic diamines, polyamides, dimer acids, and silane coupling agents. This patent significantly improves the adhesion efficiency to non-polar materials and shortens the open time by controlling the dimer acid-based polyamide formulation and precise polycondensation process. However, the formulation uses multiple special monomers, which undoubtedly increases the raw material cost and also has the disadvantage of complex preparation process. CN 119505739A, through the selection of raw materials and the design of macromolecular structure, utilizes the large amount of {C2H4} in long-chain alkyl esters of acrylic acid. n The chain segment achieves good wetting and adhesion to low polarity substrates, solving the problem of difficult adhesion of low surface energy materials. However, it is made from pure acrylic monomers and polymerized by free radicals, so its molecular weight is difficult to control and tends to be too large, which has a certain impact on subsequent applications.
[0004] Therefore, there is an urgent need to develop a structural polyester with a simple and controllable process, which can be used as the main material to synthesize a non-polar substrate adhesive to solve the problem of low adhesion to non-polar substrates PP / PE. Summary of the Invention
[0005] In order to overcome the shortcomings of the prior art, the present invention aims to provide an acrylate-modified polyester resin with excellent adhesion to low surface energy materials and its preparation method.
[0006] To achieve the above objectives, the present invention adopts the following technical solution:
[0007] The first objective of this invention is to provide a method for preparing acrylate-modified polyester resin, the method comprising the following steps:
[0008] (1) An acid anhydride with multiple functional groups undergoes an esterification reaction with a long-chain unsaturated monofunctional alcohol to obtain an unsaturated intermediate;
[0009] (2) The unsaturated intermediate obtained in step (1) is subjected to esterification reaction with dibasic acid and diol, followed by polycondensation reaction to obtain a polyester resin intermediate containing unsaturated double bonds.
[0010] (3) The polyester resin intermediate containing unsaturated double bonds obtained in step (2) is subjected to free radical polymerization reaction with acrylate monomers to obtain the acrylate-modified polyester resin.
[0011] Wherein, the acid anhydride having multiple functional groups is selected from trimellitic anhydride and / or pyromellitic dianhydride;
[0012] The long-chain unsaturated monofunctional alcohol is selected from the compounds shown in formula (I):
[0013]
[0014] R1 is an alkane segment with more than 6 carbon atoms.
[0015] Preferably, R1 is an alkane segment with 6 to 22 carbon atoms, and more preferably an alkane segment with 6 to 12 carbon atoms;
[0016] Preferably, the long-chain unsaturated monofunctional alcohol is selected from one or more of 8-nonen-1-ol, 9-decen-1-ol, 10-undecen-1-ol, and 11-dodecen-1-ol.
[0017] Preferably, in step (1), the molar ratio of the anhydride group in the polyfunctional anhydride to the hydroxyl group in the long-chain unsaturated monofunctional alcohol is 1 to 1.1:1.
[0018] Preferably, in step (3), the acrylate monomer is selected from compounds represented by formula (II):
[0019]
[0020] R2 is selected from hydrogen and C. 1~6 Alkyl groups;
[0021] R3 is a straight-chain or branched alkane segment with more than 10 carbon atoms.
[0022] Preferably, R2 is selected from hydrogen and C. 1~3 The alkyl group, preferably hydrogen or methyl;
[0023] R3 is a straight-chain or branched alkane segment with 10 to 30 carbon atoms, preferably a straight-chain or branched alkane segment with 10 to 22 carbon atoms.
[0024] Preferably, the acrylate monomer is selected from one or more of isodecyl acrylate, lauryl acrylate, lauryl methacrylate, octadecyl acrylate, octadecyl methacrylate, and docosyl acrylate.
[0025] Preferably, the molar ratio of the acrylate monomer to the long-chain unsaturated monofunctional alcohol is 0.6 to 0.8:1.
[0026] Preferably, in step (2), the molar ratio of the long-chain unsaturated monofunctional alcohol to the dicarboxylic acid is 0.5 to 0.8:1;
[0027] Preferably, the molar ratio of the diol, the dicarboxylic acid, and the anhydride with multiple functional groups is 1.3 to 2.0:1.
[0028] Preferably, the dicarboxylic acid is selected from one or more of terephthalic acid, isophthalic acid, adipic acid, sebacic acid, and dimer acids;
[0029] Preferably, the diol is selected from one or more of ethylene glycol, butanediol, 2-methyl-1,3-propanediol and hexanediol.
[0030] A second object of the present invention is to provide an acrylate-modified polyester resin obtained according to any one of the above-described preparation methods.
[0031] A third object of the present invention is to provide the use of acrylate-modified polyester resin obtained according to any of the above preparation methods or the acrylate-modified polyester resin described above in non-polar substrates.
[0032] The effects of the invention
[0033] This invention synthesizes unsaturated intermediate monomers from acid anhydrides with multiple functional groups and long-chain unsaturated monofunctional alcohols. These intermediate monomers are then further esterified and polycondensed with conventional diacids and diols to obtain polyester resin intermediates containing unsaturated double bonds. Subsequently, acrylate monomers are grafted into the resin intermediate system to obtain a modified resin with strong adhesion to non-polar substrates (such as PP or PE materials).
[0034] The preparation process provided by this invention is stable and controllable, with advantages such as controllable molecular weight, solubility in a mixed solution of toluene and butanone, transparent and uniform solution state, and stable storage. Furthermore, the polyester resin obtained by this invention can be blended with conventional polyesters (or) and isocyanates to obtain an adhesive with good adhesion to low surface energy substrates and a uniform and transparent appearance. This adhesive also exhibits good chemical resistance. Detailed Implementation
[0035] To make the technical solution and beneficial effects of the present invention more apparent and understandable, a detailed description is provided below by listing specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Any product identical or similar to the present invention, derived by any person under the guidance of the present invention or by combining the features of the present invention with other prior art, falls within the protection scope of the present invention. Unless otherwise defined, the technical and scientific terms used herein have the same meanings as those in the technical field to which this application pertains.
[0036] Unless otherwise specified, the techniques or conditions described in the following embodiments are generally performed in accordance with conventional techniques or conditions described in the literature in this field, or in accordance with the product manual and the manufacturer's recommendations.
[0037] Unless otherwise specified, all starting materials, ingredients and reagents are either commercially available or synthesized according to known methods.
[0038] The first objective of this invention is to provide a method for preparing acrylate-modified polyester resin, the method comprising the following steps:
[0039] (1) An acid anhydride with multiple functional groups undergoes an esterification reaction with a long-chain unsaturated monofunctional alcohol to obtain an unsaturated intermediate;
[0040] (2) The unsaturated intermediate obtained in step (1) is subjected to esterification reaction with dibasic acid and diol, followed by polycondensation reaction to obtain a polyester resin intermediate containing unsaturated double bonds.
[0041] (3) The polyester resin intermediate containing unsaturated double bonds obtained in step (2) is subjected to free radical polymerization reaction with acrylate monomers to obtain the acrylate-modified polyester resin.
[0042] Wherein, the acid anhydride having multiple functional groups is selected from trimellitic anhydride and / or pyromellitic dianhydride;
[0043] The long-chain unsaturated monofunctional alcohol is selected from the compounds shown in formula (I):
[0044]
[0045] In this invention, R1 represents an alkane chain segment with more than 6 carbon atoms. Long-chain unsaturated monofunctional alcohols with more than 6 carbon atoms are used; however, if the carbon chain is too short, its boiling point is too low to participate in the system reaction.
[0046] In one embodiment, R1 is an alkane segment with 6 to 22 carbon atoms, such as 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, and 22.
[0047] In one embodiment, R1 is an alkane segment with 6 to 12 carbon atoms.
[0048] In one embodiment, the long-chain unsaturated monofunctional alcohol is selected from one or more of 8-nonen-1-ol, 9-decen-1-ol, 10-undecen-1-ol, and 11-dodecen-1-ol.
[0049] In one embodiment, in step (1), the molar ratio of the anhydride group in the polyfunctional anhydride to the hydroxyl group in the long-chain unsaturated monofunctional alcohol is 1 to 1.1:1, for example, 1:1, 1.01:1, 1.02:1, 1.03:1, 1.04:1, 1.05:1, 1.06:1, 1.07:1, 1.08:1, 1.09:1, or 1.1:1.
[0050] In one embodiment, in step (1), the molar ratio of the anhydride group in the polyfunctional anhydride to the hydroxyl group in the long-chain unsaturated monofunctional alcohol is 1.01 to 1.08:1.
[0051] In this invention, the esterification reaction can be carried out in the presence of a catalyst well known to those skilled in the art. The type of catalyst is not limited in this invention, as long as it enables the above reaction to proceed smoothly and to completion. Examples of suitable catalysts in this invention include, but are not limited to, those based on titanium, tin, gallium, zinc, antimony, cobalt, manganese, germanium, alkali metals (especially lithium and sodium), alkaline earth metal compounds, aluminum compounds, combinations of aluminum compounds with lithium hydroxide or sodium hydroxide, and mixtures thereof. In one embodiment, the catalyst is based on titanium or tin.
[0052] Examples of suitable titanium compounds include tetraisopropyl titanate, bis(acetylacetonyl)diisopropyl titanate, and tetrabutyl titanate. Examples of suitable tin compounds include butyltin tri-2-ethylhexanoate, butylstannic acid, stannous oxalate, and dibutyltin oxide.
[0053] In one embodiment, in step (2), the molar ratio of the long-chain unsaturated monofunctional alcohol to the dicarboxylic acid is 0.5 to 0.8:1, for example, 0.55:1, 0.60:1, 0.65:1, 0.70:1, 0.75:1, or 0.80:1.
[0054] In one embodiment, the molar ratio of the diol, the diacid, and the anhydride having multiple functional groups is 1.3 to 2.0:1, for example, 1.4:1, 1.5:1, 1.6:1, 1.7:1, 1.8:1, 1.9:1, or 2:1.
[0055] In one embodiment, the molar ratio of the diol to the diacid is 1.5 to 3.5:1, for example, 1.4:1, 1.5:1, 1.6:1, 1.7:1, 1.8:1, 1.9:1, 2:1, 2.1:1, 2.2:1, 2.3:1, 2.4:1, 2.5:1, 2.6:1, 2.7:1, 2.8:1, 2.9:1, 3:1, 3.1:1, 3.2:1, 3.3:1, 3.4:1, or 3.5:1.
[0056] In one embodiment, the dicarboxylic acid is selected from one or more of terephthalic acid, isophthalic acid, adipic acid, sebacic acid, and dimer acids.
[0057] In one embodiment, the diol is selected from one or more of ethylene glycol, butanediol, 2-methyl-1,3-propanediol, and hexanediol.
[0058] In this invention, the polycondensation reaction in step (2) can be carried out in the presence of a stabilizer known to those skilled in the art. The type of stabilizer is not limited in this invention, as long as it enables the above reaction to proceed smoothly. In this invention, a suitable stabilizer is a phosphorus-based stabilizer. Examples of suitable phosphorus-based stabilizers include phosphoric acid, trimethyl phosphate, triethyl phosphate, triphenyl phosphate, and triethyl phosphonoacetate. Step (2) yields an unsaturated polyester matrix resin with a long side chain, and the double bond is located at the end of the side chain, exhibiting high reactivity.
[0059] In one embodiment, in step (3), the acrylate monomer is selected from compounds represented by formula (II):
[0060]
[0061] R2 is selected from hydrogen and C. 1~6 Alkyl groups;
[0062] R3 is a straight-chain or branched alkane segment with more than 10 carbon atoms.
[0063] In one embodiment, R2 is selected from hydrogen and C. 1~3 Alkyl groups.
[0064] In one embodiment, R2 is hydrogen or methyl;
[0065] In one embodiment, R3 is a straight-chain or branched alkane segment with 10 to 30 carbon atoms. By controlling the number of C atoms in long-chain acrylate to be greater than or equal to 10, the present invention further reduces the overall polarity of the polyester and further improves the adhesion performance of the polyester resin to substrates with low surface energy.
[0066] In one embodiment, R3 is a straight-chain or branched alkane segment with 10 to 22 carbon atoms.
[0067] In one embodiment, the acrylate monomer is selected from one or more of isodecanyl acrylate, lauryl acrylate, lauryl methacrylate, octadecyl acrylate, octadecyl methacrylate, and docosyl acrylate.
[0068] In one embodiment, the molar ratio of the acrylate monomer to the long-chain unsaturated monofunctional alcohol is 0.6 to 0.8:1, for example, 0.61, 0.62, 0.63, 0.64, 0.65, 0.67, 0.68, 0.69, 0.7, 0.71, 0.72, 0.73, 0.74, 0.75, 0.76, 0.77, 0.78, 0.80, etc.
[0069] In this invention, the grafting reaction of acrylate monomers can be carried out in the presence of solvents and initiators well known to those skilled in the art. The type of initiator is not limited in this invention, as long as it enables the above reaction to proceed smoothly. Suitable initiators in this invention are azo compounds or peroxides.
[0070] Examples of suitable azo compounds include azobisisobutyronitrile (AIBN), azobiscyanopentanoic acid (ACVA), 1,1'-azobis(cyclohexanecarboxynitrile) (ACHN), and α-phenylazotriphenylmethane.
[0071] Examples of suitable peroxides include dibenzoxyl peroxide, dicumyl peroxide, diacetyl peroxide, dilauryl peroxide, di-tert-butyl peroxide, and tert-butyl benzoic acid peroxide.
[0072] In this invention, suitable solvents are selected from one or more of ketone solvents, aromatic hydrocarbon solvents, and ester solvents. Examples of suitable aromatic hydrocarbon solvents include toluene. Examples of suitable ester solvents include ethyl acetate and butyl acetate. Examples of suitable ketone solvents include butanone.
[0073] There are no special restrictions on the operating temperature and time in steps (1) to (3) above, as long as the reaction can proceed smoothly and be completed. For example, in step (1), the esterification reaction to form the unsaturated intermediate can be carried out at about 130 to 200°C, preferably at 155 to 180°C; after the reaction is completed, the temperature is lowered to 90 to 110°C, preferably to 95 to 105°C; in step (2), a dicarboxylic acid and a diol are added to the system and the esterification reaction is carried out at 200 to 280°C, preferably at 230 to 245°C; then a polycondensation reaction is carried out at 180 to 260°C, preferably at 200 to 240°C; in step (3), the grafting reaction can be carried out at 60 to 100°C, preferably at 60 to 80°C.
[0074] This invention employs a stepwise feeding method. Under nitrogen protection, polyfunctional anhydrides, long-chain unsaturated monofunctional alcohols, and catalysts are first added to a stainless steel reactor in proportion. The reaction pressure is set to 0.1 MPa, the stirring rate is 60–100 r / min, and esterification is carried out at a rate of 1–2 °C / min, with the maximum temperature reaching 155–180 °C. When the hydroxyl value of the sample is less than 5 mg KOH / g, a second feeding is performed, adding the remaining diol and diacid to the reactor. The temperature is further increased to 230–245 °C. When the temperature at the top of the reactor is below 90 °C, a sample is taken to test the acid value. Esterification ends when the acid value is less than 10 mg KOH / g.
[0075] Adding additives to the esterification product, maintaining polycondensation at 200-240℃, stirring at 40-100 r / min, and vacuum less than 100 Pa, and polycondensing to the corresponding current power yields the polyester resin intermediate.
[0076] The above-mentioned polyester resin intermediate was dissolved in a mixed solvent of toluene and methyl ethyl ketone to form a solution with a solid content of 50% to 60%. Under the condition of 60 to 100°C, the initiator and long-chain acrylic acid were added dropwise to carry out a grafting reaction, thereby obtaining the acrylate-modified polyester resin of this application.
[0077] A second object of the present invention is to provide an acrylate-modified polyester resin obtained according to any one of the above-described preparation methods.
[0078] A third object of the present invention is to provide the use of acrylate-modified polyester resin obtained according to any of the above preparation methods or the acrylate-modified polyester resin described above in non-polar substrates.
[0079] The present invention will be further described below with reference to specific embodiments and comparative examples. Unless otherwise specified, specific techniques or conditions in the following embodiments are generally performed according to conventional techniques or conditions described in the literature in the art, or according to the product instructions and the manufacturer's recommendations. Unless otherwise specified, all starting materials, materials, and reagents are commercially available or synthesized according to known methods.
[0080] Example 1
[0081] In a 2L reactor under nitrogen protection, a stepwise feeding method was used. First, 152.25g of trimellitic anhydride, 111.13g of 8-nonen-1-ol, and 0.1g of tetrabutyl titanate were added to the reactor. The reaction pressure was set to 0.1 MPa, the stirring rate to 100 r / min, and the temperature was increased at a rate of 1℃ / min until the maximum temperature reached 170℃. When the hydroxyl value of the sample was less than 5mgKOH / g, a second feeding was performed. The temperature was then lowered to 100℃, and 78.99g of terephthalic acid, 138.96g of adipic acid, 59.02g of ethylene glycol, and 28.56g of... 2-Methyl-1,3-propanediol and 231.08g neopentyl glycol were added to the reactor. The stirring rate was 100r / min, and the temperature was increased at a rate of 1℃ / min for esterification. The temperature was continued to rise to 235℃. When the temperature at the top of the reactor was lower than 90℃, the acid value was tested. The esterification was ended when the acid value was less than 10mg KOH / g.
[0082] Add 0.1g of trimethyl phosphate to the esterification product, maintain polycondensation at 220℃, stir at 80r / min, and vacuum less than 100Pa, and polycondense until the hydroxyl value of the sample is 25-35mg KOH / g to obtain the matrix resin.
[0083] The matrix resin was dissolved in a 1:1 mixture of toluene and methyl ethyl ketone (MEK) to form a 60% solids solution. At 70°C, 10g of initiator AIBN was dissolved in 25g of the 1:1 mixture of toluene and MEK, and 180.02g of octadecyl acrylate was dissolved in 50g of the 1:1 mixture of toluene and MEK. These were added dropwise to initiate the grafting reaction. The reaction was stopped after 2 hours. The solids content of the sample was then tested. A 1:1 mixture of toluene and MEK was added to prepare a final sample with a 40% solids content for testing.
[0084] Example 2
[0085] In a 2L reactor under nitrogen protection, a stepwise feeding method was used. First, 116.55g of pyromellitic anhydride, 154.48g of 9-decen-1-ol, and 0.1g of tetrabutyl titanate were added to the reactor. The reaction pressure was set to 0.1 MPa, the stirring rate to 100 r / min, and the temperature was increased at a rate of 1℃ / min until the maximum temperature reached 170℃. When the hydroxyl value of the sample was less than 5mgKOH / g, a second feeding was performed. The temperature was then lowered to 100℃, and 53.26g of terephthalic acid, 35.51g of isophthalic acid, 78.09g of adipic acid, 108.07g of sebacic acid, 59.7g of ethylene glycol, and 38.52g of... 2-Methyl-1,3-propanediol and 155.82g neopentyl glycol were added to the reactor. The stirring rate was 100r / min, and the temperature was increased at a rate of 1℃ / min for esterification. The temperature was continued to rise to 235℃. When the temperature at the top of the reactor was lower than 90℃, the acid value was tested. The esterification was ended when the acid value was less than 10mg KOH / g.
[0086] Add 0.1g of trimethyl phosphate to the esterification product, maintain polycondensation at 220℃, stir at 60r / min, and vacuum less than 100Pa, and polycondense until the hydroxyl value of the sample is 25-35mg KOH / g to obtain the matrix resin.
[0087] The above-mentioned matrix resin was dissolved in a mixed solvent of toluene and methyl ethyl ketone (1:1 volume ratio) to form a solution with a solid content of 60%. Under conditions of 70°C, 10g of initiator AIBN was dissolved in 25g of mixed solvent (1:1 volume ratio of toluene and methyl ethyl ketone), and 264.41g of docosyl acrylate was dissolved in 50g of mixed solvent (1:1 volume ratio of toluene and methyl ethyl ketone). The solutions were added dropwise to carry out the grafting reaction. After the addition was completed, the reaction was stopped after 2 hours. The solid content of the sample was tested. The mixed solvent (1:1 volume ratio of toluene and methyl ethyl ketone) was added toluene and methyl ethyl ketone to finally prepare a sample with a solid content of 40% for testing.
[0088] Example 3
[0089] In a 2L reactor under nitrogen protection, a stepwise feeding method was used. First, 150.07g of trimellitic anhydride, 109.55g of 8-nonen-1-ol, and 0.1g of tetrabutyl titanate were added to the reactor. The reaction pressure was set to 0.1 MPa, the stirring rate to 100 r / min, and the temperature was increased at a rate of 1℃ / min until the maximum temperature reached 170℃. When the hydroxyl value of the sample was less than 5 mg KOH / g, a second feeding was performed. The temperature was then lowered to 100℃, and 77.86g of terephthalic acid, 148.4g of adipic acid, 58.18g of ethylene glycol, and 28.16g of... 2-Methyl-1,3-propanediol and 227.79g neopentyl glycol were added to the reactor. The stirring rate was 100r / min, and the temperature was increased at a rate of 1℃ / min for esterification. The temperature was continued to rise to 235℃. When the temperature at the top of the reactor was lower than 90℃, the acid value was tested. The esterification was ended when the acid value was less than 10mg KOH / g.
[0090] Add 0.1g of trimethyl phosphate to the esterification product, maintain polycondensation at 220℃, stir at 80r / min, and vacuum less than 100Pa, and polycondense until the hydroxyl value of the sample is 25-35mg KOH / g to obtain the matrix resin.
[0091] The above-mentioned matrix resin was dissolved in a mixed solvent of toluene and methyl ethyl ketone (1:1 volume ratio) to form a solution with a solid content of 60%. Under conditions of 70°C, 10g of initiator AIBN was dissolved in 25g of mixed solvent (1:1 volume ratio of toluene and methyl ethyl ketone), and 131.43g of lauryl acrylate was dissolved in 50g of mixed solvent (1:1 volume ratio of toluene and methyl ethyl ketone). The solutions were added dropwise to carry out the grafting reaction. After the addition was completed, the reaction was stopped after 2 hours. The solid content of the sample was tested, and the mixed solvent (1:1 volume ratio of toluene and methyl ethyl ketone) was added to finally prepare a sample with a solid content of 40% for testing.
[0092] Example 4
[0093] In a 2L reactor under nitrogen protection, a stepwise feeding method was used. First, 169.34g of trimellitic anhydride, 123.61g of 8-nonen-1-ol, and 0.1g of tetrabutyl titanate were added to the reactor. The reaction pressure was set to 0.1 MPa, the stirring rate to 100 r / min, and the temperature was increased at a rate of 1℃ / min until the maximum temperature reached 170℃. When the hydroxyl value of the sample was less than 5 mg KOH / g, a second feeding was performed. The temperature was then lowered to 100℃, and 58.57g of terephthalic acid, 115.92g of adipic acid, 43.77g of ethylene glycol, and 31.77g of... 2-Methyl-1,3-propanediol and 257.02g neopentyl glycol were added to the reactor. The stirring rate was 100r / min, and the temperature was increased at a rate of 1℃ / min for esterification. The temperature was continued to rise to 235℃. When the temperature at the top of the reactor was lower than 90℃, the acid value was tested. The esterification was ended when the acid value was less than 10mg KOH / g.
[0094] Add 0.1g of trimethyl phosphate to the esterification product, maintain polycondensation at 220℃, stir at 80r / min, and vacuum less than 100Pa, and polycondense until the hydroxyl value of the sample is 25-35mg KOH / g to obtain the matrix resin.
[0095] The above-mentioned matrix resin was dissolved in a mixed solvent of toluene and methyl ethyl ketone (1:1 volume ratio) to form a solution with a solid content of 60%. Under conditions of 70°C, 10g of initiator AIBN was dissolved in 25g of mixed solvent (1:1 volume ratio of toluene and methyl ethyl ketone), and 200.23g of octadecyl acrylate was dissolved in 50g of mixed solvent (1:1 volume ratio of toluene and methyl ethyl ketone). The solutions were added dropwise to carry out the grafting reaction. After the addition was completed, the reaction was stopped after 2 hours. The solid content of the sample was tested, and the mixed solvent (1:1 volume ratio of toluene and methyl ethyl ketone) was added to finally prepare a sample with a solid content of 40% for testing.
[0096] Example 5
[0097] In a 2L reactor under nitrogen protection, a stepwise feeding method was used. First, 152.25g of trimellitic anhydride, 111.13g of 8-nonen-1-ol, and 0.1g of tetrabutyl titanate were added to the reactor. The reaction pressure was set to 0.1 MPa, the stirring rate to 100 r / min, and the temperature was increased at a rate of 1℃ / min until the maximum temperature reached 170℃. When the hydroxyl value of the sample was less than 5mgKOH / g, a second feeding was performed. The temperature was then lowered to 100℃, and 78.99g of terephthalic acid, 138.96g of adipic acid, 59.02g of ethylene glycol, and 28.56g of... 2-Methyl-1,3-propanediol and 231.08g neopentyl glycol were added to the reactor. The stirring rate was 100r / min, and the temperature was increased at a rate of 1℃ / min for esterification. The temperature was continued to rise to 235℃. When the temperature at the top of the reactor was lower than 90℃, the acid value was tested. The esterification was ended when the acid value was less than 10mg KOH / g.
[0098] Add 0.1g of trimethyl phosphate to the esterification product, maintain polycondensation at 220℃, stir at 80r / min, and vacuum less than 100Pa, and polycondense until the hydroxyl value of the sample is 25-35mg KOH / g to obtain the matrix resin.
[0099] The above-mentioned matrix resin was dissolved in a mixed solvent of toluene and methyl ethyl ketone (1:1 volume ratio) to form a solution with a solid content of 60%. Under conditions of 70°C, 10g of initiator AIBN was dissolved in 25g of mixed solvent (1:1 volume ratio of toluene and methyl ethyl ketone), and 154.3g of octadecyl acrylate was dissolved in 50g of mixed solvent (1:1 volume ratio of toluene and methyl ethyl ketone). The solutions were added dropwise to carry out the grafting reaction. After the addition was completed, the reaction was stopped after 2 hours. The solid content of the sample was tested. The mixed solvent (1:1 volume ratio of toluene and methyl ethyl ketone) was added toluene and methyl ethyl ketone to finally prepare a sample with a solid content of 40% for testing.
[0100] Example 6
[0101] In a 2L reactor under nitrogen protection, a stepwise feeding method was used. First, 152.25g of trimellitic anhydride, 111.13g of 8-nonen-1-ol, and 0.1g of tetrabutyl titanate were added to the reactor. The reaction pressure was set to 0.1 MPa, the stirring rate to 100 r / min, and the temperature was increased at a rate of 1℃ / min until the maximum temperature reached 170℃. When the hydroxyl value of the sample was less than 5mgKOH / g, a second feeding was performed. The temperature was then lowered to 100℃, and 78.99g of terephthalic acid, 138.96g of adipic acid, 59.02g of ethylene glycol, and 28.56g of... 2-Methyl-1,3-propanediol and 231.08g neopentyl glycol were added to the reactor. The stirring rate was 100r / min, and the temperature was increased at a rate of 1℃ / min for esterification. The temperature was continued to rise to 235℃. When the temperature at the top of the reactor was lower than 90℃, the acid value was tested. The esterification was ended when the acid value was less than 10mg KOH / g.
[0102] Add 0.1g of trimethyl phosphate to the esterification product, maintain polycondensation at 220℃, stir at 80r / min, and vacuum less than 100Pa, and polycondense until the hydroxyl value of the sample is 25-35mg KOH / g to obtain the matrix resin.
[0103] The above-mentioned matrix resin was dissolved in a mixed solvent of toluene and methyl ethyl ketone (1:1 volume ratio) to form a solution with a solid content of 60%. Under conditions of 70°C, 10g of initiator AIBN was dissolved in 25g of mixed solvent (1:1 volume ratio of toluene and methyl ethyl ketone), and 198.02g of octadecyl acrylate was dissolved in 50g of mixed solvent (1:1 volume ratio of toluene and methyl ethyl ketone). The solutions were added dropwise to carry out the grafting reaction. After the addition was completed, the reaction was stopped after 2 hours. The solid content of the sample was tested, and the mixed solvent (1:1 volume ratio of toluene and methyl ethyl ketone) was added to finally prepare a sample with a solid content of 40% for testing.
[0104] Example 7
[0105] In a 2L reactor under nitrogen protection, a stepwise feeding method was used. First, 150.19g of trimellitic anhydride, 120.45g of 9-decen-1-ol, and 0.1g of tetrabutyl titanate were added to the reactor. The reaction pressure was set to 0.1 MPa, the stirring rate to 100 r / min, and the temperature was increased at a rate of 1℃ / min until the maximum temperature reached 170℃. When the hydroxyl value of the sample was less than 5 mg KOH / g, a second feeding was performed. The temperature was then lowered to 100℃, and 77.92g of terephthalic acid, 137.09g of adipic acid, 58.22g of ethylene glycol, and 28.18g of... 2-Methyl-1,3-propanediol and 227.96g neopentyl glycol were added to the reactor. The stirring rate was 100r / min, and the temperature was increased at a rate of 1℃ / min for esterification. The temperature was continued to rise to 235℃. When the temperature at the top of the reactor was lower than 90℃, the acid value was tested. The esterification was ended when the acid value was less than 10mg KOH / g.
[0106] Add 0.1g of trimethyl phosphate to the esterification product, maintain polycondensation at 220℃, stir at 80r / min, and vacuum less than 100Pa, and polycondense until the hydroxyl value of the sample is 25-35mg KOH / g to obtain the matrix resin.
[0107] The matrix resin was dissolved in a mixture of toluene and methyl ethyl ketone (MEK) in a 1:1 volume ratio to form a solution with a solid content of 60%. At 70°C, 10g of initiator AIBN was dissolved in 25g of the mixed solvent (toluene and MEK in a 1:1 volume ratio), and 208.29g of docosyl acrylate was dissolved in 50g of the mixed solvent (toluene and MEK in a 1:1 volume ratio). These were added dropwise to initiate the grafting reaction. After the addition was complete, the reaction was stopped after 2 hours. The solid content of the sample was then tested. The mixed solvent (toluene and MEK in a 1:1 volume ratio) was then added to prepare a final sample with a 40% solid content for testing.
[0108] Example 8
[0109] In a 2L reactor under nitrogen protection, a stepwise feeding method was used. First, 152.25g of trimellitic anhydride, 111.13g of 8-nonen-1-ol, and 0.1g of tetrabutyl titanate were added to the reactor. The reaction pressure was set to 0.1 MPa, the stirring rate to 100 r / min, and the temperature was increased at a rate of 1℃ / min until the maximum temperature reached 170℃. When the hydroxyl value of the sample was less than 5mgKOH / g, a second feeding was performed. The temperature was then lowered to 100℃, and 78.99g of terephthalic acid, 138.96g of adipic acid, 59.02g of ethylene glycol, and 28.56g of... 2-Methyl-1,3-propanediol and 231.08g neopentyl glycol were added to the reactor. The stirring rate was 100r / min, and the temperature was increased at a rate of 1℃ / min for esterification. The temperature was continued to rise to 235℃. When the temperature at the top of the reactor was lower than 90℃, the acid value was tested. The esterification was ended when the acid value was less than 10mg KOH / g.
[0110] Add 0.1g of trimethyl phosphate to the esterification product, maintain polycondensation at 220℃, stir at 80r / min, and vacuum less than 100Pa, and polycondense until the hydroxyl value of the sample is 25-35mg KOH / g to obtain the matrix resin.
[0111] The above-mentioned matrix resin was dissolved in a mixed solvent of toluene and methyl ethyl ketone (1:1 volume ratio) to form a solution with a solid content of 60%. Under conditions of 70°C, 10g of initiator AIBN was dissolved in 25g of mixed solvent (1:1 volume ratio of toluene and methyl ethyl ketone), and 133.34g of lauryl acrylate was dissolved in 50g of mixed solvent (1:1 volume ratio of toluene and methyl ethyl ketone). The solutions were added dropwise to carry out the grafting reaction. After the addition was completed, the reaction was stopped after 2 hours. The solid content of the sample was tested, and the mixed solvent (1:1 volume ratio of toluene and methyl ethyl ketone) was added to finally prepare a sample with a solid content of 40% for testing.
[0112] Comparative Example 1
[0113] In a 2L reactor under nitrogen protection, a stepwise feeding method was used. First, 151.73g of trimellitic anhydride, 113.46g of 8-nonen-1-ol, and 0.1g of tetrabutyl titanate were added to the reactor. The reaction pressure was set to 0.1 MPa, the stirring rate to 100 r / min, and the temperature was increased at a rate of 1℃ / min until the maximum temperature reached 170℃. When the hydroxyl value of the sample was less than 5mgKOH / g, a second feeding was performed. The temperature was then lowered to 100℃, and 78.72g of terephthalic acid, 138.5g of adipic acid, 58.82g of ethylene glycol, and 28.47g of... 2-Methyl-1,3-propanediol and 230.3g neopentyl glycol were added to the reactor. The stirring rate was 100r / min, and the temperature was increased at a rate of 1℃ / min for esterification. The temperature was continued to rise to 235℃. When the temperature at the top of the reactor was lower than 90℃, the acid value was tested. The esterification was ended when the acid value was less than 10mg KOH / g.
[0114] Add 0.1g of trimethyl phosphate to the esterification product, maintain polycondensation at 220℃, stir at 80r / min, and vacuum less than 100Pa, and polycondense until the hydroxyl value of the sample is 25-35mg KOH / g to obtain the matrix resin.
[0115] The matrix resin was dissolved in a mixture of toluene and methyl ethyl ketone (MEK) in a 1:1 volume ratio to form a solution with a solid content of 60%. At 70°C, 10g of initiator AIBN was dissolved in 25g of the mixed solvent (toluene and MEK in a 1:1 volume ratio), and 179.41g of octadecyl acrylate was dissolved in 50g of the mixed solvent (toluene and MEK in a 1:1 volume ratio). These were added dropwise to initiate the grafting reaction. After the addition was complete, the reaction was stopped after 2 hours. The solid content of the sample was then tested. The mixed solvent (toluene and MEK in a 1:1 volume ratio) was then added to prepare a final sample with a 40% solid content for testing.
[0116] Comparative Example 2
[0117] In a 2L reactor under nitrogen protection, a stepwise feeding method was used. First, 158.77g of trimellitic anhydride, 105.79g of 8-nonen-1-ol, and 0.1g of tetrabutyl titanate were added to the reactor. The reaction pressure was set to 0.1 MPa, the stirring rate to 100 r / min, and the temperature was increased at a rate of 1℃ / min until the maximum temperature reached 170℃. When the hydroxyl value of the sample was less than 5 mg KOH / g, a second feeding was performed. The temperature was then lowered to 100℃, and 82.37g of terephthalic acid, 120.76g of adipic acid, 61.55g of ethylene glycol, and 29.79g of... 2-Methyl-1,3-propanediol and 240.98g neopentyl glycol were added to the reactor. The stirring rate was 100r / min, and the temperature was increased at a rate of 1℃ / min for esterification. The temperature was continued to rise to 235℃. When the temperature at the top of the reactor was lower than 90℃, the acid value was tested. The esterification was ended when the acid value was less than 10mg KOH / g.
[0118] Add 0.1g of trimethyl phosphate to the esterification product, maintain polycondensation at 220℃, stir at 80r / min, and keep the vacuum degree less than 100Pa. Polycondense until the hydroxyl value of the sample is 25-35mg KOH / g to obtain the matrix resin. The sample reaction is prone to crosslinking, and multiple experiments are required to obtain the target sample.
[0119] The matrix resin was dissolved in a mixture of toluene and methyl ethyl ketone (MEK) in a 1:1 volume ratio to form a solution with a solid content of 60%. At 70°C, 10g of initiator AIBN was dissolved in 25g of the mixed solvent (toluene and MEK in a 1:1 volume ratio), and 187.73g of octadecyl acrylate was dissolved in 50g of the mixed solvent (toluene and MEK in a 1:1 volume ratio). These were added dropwise to initiate the grafting reaction. After the addition was complete, the reaction was stopped after 2 hours. The solid content of the sample was then tested. The mixed solvent (toluene and MEK in a 1:1 volume ratio) was then added to prepare a final sample with a 40% solid content for testing.
[0120] Comparative Example 3
[0121] In a 2L reactor under nitrogen protection, a stepwise feeding method was used. First, 144.82g of trimellitic anhydride, 105.72g of 8-nonen-1-ol, and 0.1g of tetrabutyl titanate were added to the reactor. The reaction pressure was set to 0.1 MPa, the stirring rate to 100 r / min, and the temperature was increased at a rate of 1℃ / min until the maximum temperature reached 170℃. When the hydroxyl value of the sample was less than 5 mg KOH / g, a second feeding was performed. The temperature was then lowered to 100℃, and 75.14g of terephthalic acid, 158.63g of adipic acid, 56.14g of ethylene glycol, and 27.17g of... 2-Methyl-1,3-propanediol and 232.38g neopentyl glycol were added to the reactor. The stirring rate was 100r / min, and the temperature was increased at a rate of 1℃ / min for esterification. The temperature was continued to rise to 235℃. When the temperature at the top of the reactor was lower than 90℃, the acid value was tested. The esterification was ended when the acid value was less than 10mg KOH / g.
[0122] Add 0.1g of trimethyl phosphate to the esterification product, maintain polycondensation at 220℃, stir at 80r / min, and vacuum less than 100Pa, and polycondense until the hydroxyl value of the sample is 25-35mg KOH / g to obtain the matrix resin.
[0123] The above-mentioned matrix resin was dissolved in a mixed solvent of toluene and methyl ethyl ketone (1:1 volume ratio) to form a solution with a solid content of 60%. Under conditions of 70°C, 10g of initiator AIBN was dissolved in 25g of mixed solvent (1:1 volume ratio of toluene and methyl ethyl ketone), and 171.24g of octadecyl acrylate was dissolved in 50g of mixed solvent (1:1 volume ratio of toluene and methyl ethyl ketone). The solutions were added dropwise to carry out the grafting reaction. After the addition was completed, the reaction was stopped after 2 hours. The solid content of the sample was tested, and the mixed solvent (1:1 volume ratio of toluene and methyl ethyl ketone) was added to finally prepare a sample with a solid content of 40% for testing.
[0124] Comparative Example 4
[0125] In a 2L reactor under nitrogen protection, a stepwise feeding method was used. First, 184.17g of trimellitic anhydride, 134.44g of 8-nonen-1-ol, and 0.1g of tetrabutyl titanate were added to the reactor. The reaction pressure was set to 0.1 MPa, the stirring rate to 100 r / min, and the temperature was increased at a rate of 1℃ / min until the maximum temperature reached 170℃. When the hydroxyl value of the sample was less than 5 mg KOH / g, a second feeding was performed. The temperature was then lowered to 100℃, and 63.7g of terephthalic acid, 112.07g of adipic acid, 71.4g of ethylene glycol, and 34.55g of... 2-Methyl-1,3-propanediol and 199.67g neopentyl glycol were added to the reactor. The stirring rate was 100r / min, and the temperature was increased at a rate of 1℃ / min for esterification. The temperature was continued to rise to 235℃. When the temperature at the top of the reactor was lower than 90℃, the acid value was tested. The esterification was ended when the acid value was less than 10mg KOH / g.
[0126] Add 0.1g of trimethyl phosphate to the esterification product, maintain polycondensation at 220℃, stir at 80r / min, and with a vacuum of less than 100Pa. Polycondense until the hydroxyl value of the sample is 25-35mg KOH / g to obtain the matrix resin. The presence of steric hindrance makes it difficult for the Mn in the sample to expand. Prolonging the polycondensation time will result in more side reactions.
[0127] The matrix resin was dissolved in a mixture of toluene and methyl ethyl ketone (MEK) in a 1:1 volume ratio to form a solution with a solid content of 60%. At 70°C, 10g of initiator AIBN was dissolved in 25g of the mixed solvent (toluene and MEK in a 1:1 volume ratio), and 217.77g of octadecyl acrylate was dissolved in 50g of the mixed solvent (toluene and MEK in a 1:1 volume ratio). These were added dropwise to initiate the grafting reaction. After the addition was complete, the reaction was stopped after 2 hours. The solid content of the sample was then tested. The mixed solvent (toluene and MEK in a 1:1 volume ratio) was then added to prepare a final sample with a 40% solid content for testing.
[0128] Comparative Example 5
[0129] In a 2L reactor under nitrogen protection, a stepwise feeding method was used. First, 152.25g of trimellitic anhydride, 111.13g of 8-nonen-1-ol, and 0.1g of tetrabutyl titanate were added to the reactor. The reaction pressure was set to 0.1 MPa, the stirring rate to 100 r / min, and the temperature was increased at a rate of 1℃ / min until the maximum temperature reached 170℃. When the hydroxyl value of the sample was less than 5mgKOH / g, a second feeding was performed. The temperature was then lowered to 100℃, and 78.99g of terephthalic acid, 138.96g of adipic acid, 59.02g of ethylene glycol, and 28.56g of... 2-Methyl-1,3-propanediol and 231.08g neopentyl glycol were added to the reactor. The stirring rate was 100r / min, and the temperature was increased at a rate of 1℃ / min for esterification. The temperature was continued to rise to 235℃. When the temperature at the top of the reactor was lower than 90℃, the acid value was tested. The esterification was ended when the acid value was less than 10mg KOH / g.
[0130] Add 0.1g of trimethyl phosphate to the esterification product, maintain polycondensation at 220℃, stir at 80r / min, and vacuum less than 100Pa, and polycondense until the hydroxyl value of the sample is 25-35mg KOH / g to obtain the matrix resin.
[0131] The matrix resin was dissolved in a mixture of toluene and methyl ethyl ketone (MEK) in a 1:1 volume ratio to form a solution with a solid content of 60%. At 70°C, 10g of initiator AIBN was dissolved in 25g of the mixed solvent (toluene and MEK in a 1:1 volume ratio), and 149.16g of octadecyl acrylate was dissolved in 50g of the mixed solvent (toluene and MEK in a 1:1 volume ratio). These were added dropwise to initiate the grafting reaction. After the addition was complete, the reaction was stopped after 2 hours. The solid content of the sample was then tested. The mixed solvent (toluene and MEK in a 1:1 volume ratio) was then added to prepare a final sample with a 40% solid content for testing.
[0132] Comparative Example 6
[0133] In a 2L reactor under nitrogen protection, a stepwise feeding method was used. First, 152.25g of trimellitic anhydride, 111.13g of 8-nonen-1-ol, and 0.1g of tetrabutyl titanate were added to the reactor. The reaction pressure was set to 0.1 MPa, the stirring rate to 100 r / min, and the temperature was increased at a rate of 1℃ / min until the maximum temperature reached 170℃. When the hydroxyl value of the sample was less than 5mgKOH / g, a second feeding was performed. The temperature was then lowered to 100℃, and 78.99g of terephthalic acid, 138.96g of adipic acid, 59.02g of ethylene glycol, and 28.56g of... 2-Methyl-1,3-propanediol and 231.08g neopentyl glycol were added to the reactor. The stirring rate was 100r / min, and the temperature was increased at a rate of 1℃ / min for esterification. The temperature was continued to rise to 235℃. When the temperature at the top of the reactor was lower than 90℃, the acid value was tested. The esterification was ended when the acid value was less than 10mg KOH / g.
[0134] Add 0.1g of trimethyl phosphate to the esterification product, maintain polycondensation at 220℃, stir at 80r / min, and vacuum less than 100Pa, and polycondense until the hydroxyl value of the sample is 25-35mg KOH / g to obtain the matrix resin.
[0135] The matrix resin was dissolved in a mixture of toluene and methyl ethyl ketone (MEK) in a 1:1 volume ratio to form a solution with a solid content of 60%. At 70°C, 10g of initiator AIBN was dissolved in 25g of the mixed solvent (toluene and MEK in a 1:1 volume ratio), and 210.88g of octadecyl acrylate was dissolved in 50g of the mixed solvent (toluene and MEK in a 1:1 volume ratio). These were added dropwise to initiate the grafting reaction. After the addition was complete, the reaction was stopped after 2 hours. The solid content of the sample was then tested. The mixed solvent (toluene and MEK in a 1:1 volume ratio) was then added to prepare a final sample with a 40% solid content for testing.
[0136] Comparative Example 7
[0137] In a 2L reactor under nitrogen protection, a stepwise feeding method was used. First, 152.25g of trimellitic anhydride, 111.13g of 8-nonen-1-ol, and 0.1g of tetrabutyl titanate were added to the reactor. The reaction pressure was set to 0.1 MPa, the stirring rate to 100 r / min, and the temperature was increased at a rate of 1℃ / min until the maximum temperature reached 170℃. When the hydroxyl value of the sample was less than 5mgKOH / g, a second feeding was performed. The temperature was then lowered to 100℃, and 78.99g of terephthalic acid, 138.96g of adipic acid, 59.02g of ethylene glycol, and 28.56g of... 2-Methyl-1,3-propanediol and 231.08g neopentyl glycol were added to the reactor. The stirring rate was 100r / min, and the temperature was increased at a rate of 1℃ / min for esterification. The temperature was continued to rise to 235℃. When the temperature at the top of the reactor was lower than 90℃, the acid value was tested. The esterification was ended when the acid value was less than 10mg KOH / g.
[0138] Add 0.1g of trimethyl phosphate to the esterification product, maintain polycondensation at 220℃, stir at 80r / min, and vacuum less than 100Pa, and polycondense until the hydroxyl value of the sample is 25-35mg KOH / g to obtain the matrix resin.
[0139] The above-mentioned matrix resin was dissolved in a mixed solvent of toluene and methyl ethyl ketone (1:1 volume ratio) to form a solution with a solid content of 60%. Under conditions of 70°C, 10g of initiator AIBN was dissolved in 25g of mixed solvent (1:1 volume ratio of toluene and methyl ethyl ketone), and 102.22g of octyl acrylate was dissolved in 50g of mixed solvent (1:1 volume ratio of toluene and methyl ethyl ketone). The solutions were added dropwise to carry out the grafting reaction. After the addition was completed, the reaction was stopped after 2 hours. The solid content of the sample was tested. The mixed solvent (1:1 volume ratio of toluene and methyl ethyl ketone) was added to prepare a final sample with a solid content of 40% for testing.
[0140] Test case
[0141] The performance of the acrylate-modified polyester resins prepared in Examples 1-8 and Comparative Examples 1-7 was evaluated:
[0142] (1) The molecular weight, acid value, hydroxyl value, etc. of the acrylate-modified polyester resins prepared in Examples 1-8 and Comparative Examples 1-7 were tested. The test methods are as follows:
[0143] Molecular weight (Mn) was determined by Waters e2695 gel chromatography with a 2414RI detector, a Styragel HR3 5μm 7.8*300mm (THF) column, and chloroform as the mobile phase.
[0144] Acid value: GB / T 12008.5-2010 Plastics Polyether Polyols Part 5 - Determination of Acid Value.
[0145] Hydroxyl value: GB / T 12008.3-2009 Plastics Polyether Polyols Part 3 - Determination of Hydroxyl Value.
[0146] (2) The adhesion properties of the acrylate-modified polyester resins prepared in Examples 1-8 and Comparative Examples 1-7 to non-polar substrates were tested:
[0147] Using the grafted and modified solutions prepared in Examples 1-8 and Comparative Examples 1-7 above, a certain proportion of high-Tg polyester and curing agent were combined to synthesize an adhesive. The high-Tg polyester used was Hanhai New Materials AH640, AH651, CH449, etc., and the curing agent used was HDI-based such as Bayer N3300, N3390, Asahi Kasei TPA-100, TMA-100, etc. The specific adhesive formulation method is as follows:
[0148] The high Tg polyester was dissolved in a mixture of toluene and methyl ethyl ketone (volume ratio 1:1) to form a solution with a solid content of 40%. The high Tg polyester used in this invention is AH640.
[0149] 80 portions of the grafted modified solution prepared in Examples 1-8 and Comparative Examples 1-7 were selected.
[0150] 15 portions of AH640 solution
[0151] N3300 5 copies
[0152] Stir well at room temperature and set aside.
[0153] Each adhesive was used for bonding non-polar PP / PE substrates, with a substrate thickness of 40μm and an adhesive application rate of 10g / m². 2 Dry at 120℃ for 20 seconds, then laminate using a laminating machine at 70℃ and 0.3MPa. After lamination, place in a 60℃ oven for 3 days to cure. The peel strength is then examined using the following test method:
[0154] Adhesion strength test: Refer to the national standard GB / T 8808 for the test method of peel strength of adhesive tape.
[0155] Glue condition: After preparing the glue, let it stand for 1 hour and observe it with the naked eye.
[0156] Chemical resistance test: The cured sample is immersed in ethyl acetate at 60℃ for 24 hours. After being removed, it is placed in an environment of 25℃ and 50% RH for 24 hours. The appearance of the adhesive layer is observed and the peel strength is tested. The peel strength test standard is the same as before. The adhesive layer is excellent if there is no obvious whitening and the force value is maintained above 85%; the adhesive layer is medium if there is obvious whitening or the force value retention rate is 70%-85%; the adhesive layer is poor if there is blistering / peeling or the force value is less than 70%.
[0157] The measurement results are shown in Table 1.
[0158] Table 1
[0159]
[0160]
[0161] In Comparative Example 1, there was free monofunctional alcohol, and the viscosity of the matrix resin did not increase. In Comparative Example 2, the branching was severe, and the polyester resin intermediate was easy to crosslink. Due to the steric hindrance effect, the viscosity of the polyester resin intermediate in Comparative Example 4 was difficult to increase. The adhesives obtained in Comparative Examples 3, 5, 6, and 7 had poor bonding effects.
[0162] As can be seen from the above examples and comparative examples, the acrylate-modified polyester resin obtained by the present invention has excellent adhesion to non-polar substrates such as PP or PE.
[0163] It should be understood that the above embodiments are exemplary and are not intended to encompass all possible implementations included in the claims. Various modifications and changes can be made to the above embodiments without departing from the scope of this disclosure. Similarly, the various technical features of the above embodiments can be arbitrarily combined to form other embodiments of the present invention that may not be explicitly described. Therefore, the above embodiments only illustrate several implementations of the present invention and do not limit the scope of protection of this patent.
Claims
1. A method for preparing an acrylate-modified polyester resin, characterized in that, The method includes the following steps: (1) An acid anhydride with multiple functional groups undergoes esterification with a long-chain unsaturated monofunctional alcohol to obtain an unsaturated intermediate; (2) The unsaturated intermediate obtained in step (1) is subjected to esterification reaction with diacid and diol, followed by polycondensation reaction to obtain a polyester resin intermediate containing unsaturated double bonds. (3) The polyester resin intermediate containing unsaturated double bonds obtained in step (2) is subjected to free radical polymerization reaction with acrylate monomers to obtain the acrylate-modified polyester resin. Wherein, the acid anhydride having multiple functional groups is selected from trimellitic anhydride and / or pyromellitic dianhydride; The long-chain unsaturated monofunctional alcohol is selected from the compounds shown in formula (I): ; Wherein, R1 is an alkane chain segment with 6 to 22 carbon atoms; In step (3), the acrylate monomer is selected from the compounds shown in formula (II): ; R2 is selected from hydrogen or C. 1~6 Alkyl groups; R3 is a straight-chain or branched alkane segment with 10 to 30 carbon atoms; The molar ratio of the anhydride group in the polyfunctional anhydride to the hydroxyl group in the long-chain unsaturated monofunctional alcohol is 1~1.1:1; The molar ratio of the long-chain unsaturated monofunctional alcohol to the dicarboxylic acid is 0.5~0.8:1; The molar ratio of the acrylate monomer to the long-chain unsaturated monofunctional alcohol is 0.6~0.8:
1.
2. The preparation method according to claim 1, characterized in that, R1 is an alkane segment with 6 to 12 carbon atoms.
3. The preparation method according to claim 1, characterized in that, The long-chain unsaturated monofunctional alcohol is selected from one or more of 8-nonen-1-ol, 9-decen-1-ol, 10-undecen-1-ol, and 11-dodecen-1-ol.
4. The preparation method according to claim 1, characterized in that, R2 is selected from hydrogen or C. 1~3 Alkyl groups.
5. The preparation method according to claim 4, characterized in that, R2 is hydrogen or methyl; R3 is a straight-chain or branched alkane segment with 10 to 22 carbon atoms.
6. The preparation method according to claim 1, characterized in that, The acrylate monomer is selected from one or more of isodecyl acrylate, lauryl acrylate, lauryl methacrylate, octadecyl acrylate, octadecyl methacrylate, and docosyl acrylate.
7. The preparation method according to claim 1, characterized in that, The molar ratio of the diol, the dicarboxylic acid, and the anhydride with multiple functional groups is 1.3 to 2.0:
1.
8. The preparation method according to claim 1, characterized in that, The dicarboxylic acid is selected from one or more of terephthalic acid, isophthalic acid, adipic acid, sebacic acid, and dimer acids.
9. The preparation method according to claim 1, characterized in that, The diol is selected from one or more of ethylene glycol, butanediol, 2-methyl-1,3-propanediol and hexanediol.
10. An acrylate-modified polyester resin obtained by the preparation method according to any one of claims 1 to 9.
11. The application of the acrylate-modified polyester resin obtained by the preparation method according to any one of claims 1 to 9 or the acrylate-modified polyester resin according to claim 10 in a non-polar substrate.
Citation Information
Patent Citations
A polyamide hot melt adhesive with strong adhesion to non-polar materials and its preparation method
CN104893648B
Double-sided adhesive tape for pasting low-surface-energy material and preparation method of double-sided adhesive tape
CN119505739A
Polyester resin as well as preparation method and application thereof
CN119735754A
Acrylic modified polyester resin and preparation method thereof
US20210130524A1